2000
DOI: 10.1258/0956462001916263
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault and sexually transmitted infections: an updated review

Abstract: The purpose of this review is to provide an overview of sexual assault (in adults). In particular, the aim is to emphasize changes regarding medical, legal and management issues since the subject was reviewed in this journal in 1990. However some aspects will not have changed in the last 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
(21 reference statements)
1
13
0
1
Order By: Relevance
“…110 The most common STIs reported in sexual assault victims are those that are common in the population and include Chlamydia, gonorrhea, and trichomoniasis. 79, 111 The best approach to collecting specimens for STIs immediately after a sexual assault is debated. A speculum examination may be traumatic, especially for a teenager who has not had one before and may lead to avoidance of reproductive health care in the future.…”
Section: Management Of Pregnancy and Sti Risk After Sexual Assaultmentioning
confidence: 99%
“…110 The most common STIs reported in sexual assault victims are those that are common in the population and include Chlamydia, gonorrhea, and trichomoniasis. 79, 111 The best approach to collecting specimens for STIs immediately after a sexual assault is debated. A speculum examination may be traumatic, especially for a teenager who has not had one before and may lead to avoidance of reproductive health care in the future.…”
Section: Management Of Pregnancy and Sti Risk After Sexual Assaultmentioning
confidence: 99%
“…Sexual assault appears to be associated with a higher risk for acquiring an STI, with studies finding elevated rates of STIs among those who report sexual assault and high rates of sexual violence among those who report STIs, although prevalence rates range widely across studies (see Lambda &Murphy, 2000, andReynolds, Peipert, &Collins, 2000, for reviews). For instance, one study of college women found that those who reported a history of sexual assault were more likely to have a human papillomavirus (HPV) infection than those without an assault history (Kahn, Huang, Rosenthal, Tissot, & Burk, 2005).…”
mentioning
confidence: 99%
“…Infections observed in abused subjects are similar to those observed within the general population, with a prevalence of Chlamydia. A study published in 2000 reported in the UK a prevalence of infection in abused subjects of between 12.7% and 21% (Lamba and Murphy 2000). A meta-analysis published in 2000 observed a prevalence of N. gonorrhoeae of 2-6.5%, C. trachomatis 6-17%, T. vaginalis 2.3-14.7% and syphilis 1-3% (Reynolds et al 2000;Cattaneo et al 2006).…”
Section: Sexual Transmitted Infections In Adultsmentioning
confidence: 99%